Digital Storytelling and Cultural Heritage in Sarawak Destination Marketing - Lee, Qin Yi (Curtin University, 2024)
This research aims to develop exemplary storylines combining cultural heritage and touristic experiences. The research outcome provides practical guidelines for storytelling in a digital context, addressing the issues and challenges faced in integrating digital storytelling and promoting tourism experiences of local and regional cultural heritage. Ultimately, this study aims to increase visitor engagement and interest and enhance Malaysia’s competitive position as a future tourism destination by embracing digital storytelling and cultural heritage.